Community Satisfaction Index Analysis At The Services Of The Ulu Manna Camat Office South Bengkulu District - Marleni, Lena (Journal of Management, Economic, and Accounting, 2022)
Bengkulu Selatan provides services for free at no charge. The lowest satisfaction value is 2.30, namely facilities and infrastructure with poor assessment criteria. This illustrates that adequate facilities are not yet available, such as a manual queuing system and insufficient chairs in the waiting room, so people have to stand waiting in line.Keywords: Community Satisfaction Index, Service Public services are often needed in the form of public goods and public services. Examples of services in the form of public goods include roads, clean water, electricity and so on, while examples of services in the form of public services include administrative, health, education and transportation services. Public services are provided to the community. The purpose of this study was to analyze the Community Satisfaction Index in the Services of the Ulu Manna Sub-district Office, South Bengkulu Regency.This research is categorized as descriptive quantitative research. Sampling was done by accidental sampling technique. Collecting data using a questionnaire and the analytical method used is by measuring the value of the Community Satisfaction Index (IKM) based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 concerning Guidelines for Compiling a Community Satisfaction Survey for Public Service Providers which is calculated using the value weighted average of each service element.The value of the Community Satisfaction Index (IKM) for the quality of public services at the Ulu Manna Sub-district Office, South Bengkulu Regency is 74.75 with service quality C and the assessment of service unit performance is "Poor Good" because it is in the interval value of 65.00 - 76.60. This shows that people who receive services from the Ulu Manna Sub-district Office, South Bengkulu Regency, consider the services provided by the Ulu Manna Sub-district Office, South Bengkulu Regency to be less satisfied with the community. The element of cost/tariff gets the highest rating with an average value of 3.49 with good assessment criteria. This illustrates that the community evaluates the Ulu Manna District Office for Public